Project scheduling analysis using critical path method and program evaluation review technique - Farrel Lucky; Muthia Roza Linda (Operations Management and Information System Studies, 2022)
Infrastructure development is usually known as a project. Projects can be interpreted as activities that take place within a limited period by allocating specific resources and are intended to produce the product of deliverables whose quality criteria have been clearly outlined. Unplanned project activities and ineffective control often cause the success or failure of project implementation, so project activities are inefficient. It caused delays, decreased quality of work, and cost overruns. Project scheduling is a critical aspect of evaluating the project's sustainability from cost and time of completion as this research at PT Royal Bridea Indonesia used the CPM and PERT methods. The results obtained from the CPM method are that a project with a duration of 195 days can be completed in 164 days with a required cost of IDR 202,967,246. While with the PERT method, the project can be completed in 166 days at the cost of IDR 200,124,020.